PROSES PERANCANGAN PENGEMBANGAN MEDIA STORYBOARD TERHADAP PEMBELAJARAN MENGGALI INFORMASI BUKU FIKSI DAN NON FIKSI PADA BAHASA INDONESIA - Siti Aisyah; Abu Yazid Adnan Quthny; Hemas Haryas Harja Susetya (FKIP, Universitas Billfath Lamongan, 2022)
This development research aims to determine the process of developing or designing storyboard media for learning to explore and find information on fiction and non-fiction books. The research model used is the Borg and Gall development model. The difference is that this time the researcher only focuses on the development of storyboard media before it is realized in learning. Based on the explanation that the research has written, the process of making storyboard media has several stages, namely through design, design, then at the stage of product development or learning media. The data collection technique of this research was obtained from the validation value of media and material experts. The results showed that storyboard media was very valid to use with an average acquisition of 72. Storyboard learning media can be explained that storyboard media in the form of comics or story books can be a reference in learning related to literacy in Indonesian language learning. Based on these data, the storyboard media can be said to be of high quality because it meets the appropriate criteria. Based on the results of the study, the authors suggest that storyboard media be used in exploring and finding information on fiction and non-fiction books because it will be easy to understand h. So that students can increase motivation and interest in reading.